2020
DOI: 10.1021/acs.jafc.0c02555
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum fusiforme Fucoidan Alleviates High-Fat Diet-Induced Obesity and Insulin Resistance Associated with the Improvement of Hepatic Oxidative Stress and Gut Microbiota Profile

Abstract: Sargassum f usiforme fucoidan (SFF) exhibits diverse biological activities. Insulin resistance (IR) implicated in type 2 diabetes (T2D) has become an epidemic health issue worldwide. In this study, we investigated whether SFF can improve insulin sensitivity in high-fat diet (HFD)-fed mice. Our present data showed that SFF significantly reduced fasting blood glucose and IR index along with improved glucose tolerance. Impaired phosphorylation of Akt was also restored by SFF. Furthermore, SFF decreased the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 65 publications
4
51
0
Order By: Relevance
“…Fucoidan from S. fusiforme changed the gut microbiota, particularly by increasing the Bacteroidetes to Firmicutes ratio, to decrease streptozotocin-induced hyperglycaemia in mice [ 48 ]. Further, fucoidan from S. fusiforme decreased high-fat-diet-induced insulin resistance in mice by activating the Nrf2 pathway, changing the gut microbiota and reducing intestinal inflammation [ 49 ]. Fucoidan supplementation of 100 mg/kg/day in high-fat-diet-fed rats improved blood lipid concentrations, decreased fat deposition in the liver and changed the gut microbiota [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan from S. fusiforme changed the gut microbiota, particularly by increasing the Bacteroidetes to Firmicutes ratio, to decrease streptozotocin-induced hyperglycaemia in mice [ 48 ]. Further, fucoidan from S. fusiforme decreased high-fat-diet-induced insulin resistance in mice by activating the Nrf2 pathway, changing the gut microbiota and reducing intestinal inflammation [ 49 ]. Fucoidan supplementation of 100 mg/kg/day in high-fat-diet-fed rats improved blood lipid concentrations, decreased fat deposition in the liver and changed the gut microbiota [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the ethanoic extracts of Garcinia brasiliensis can effectively reduce the growth of Firmicutes and Proteobacteria together with the expressions of an oxidative stress marker malondialdehyde (Ara ujo et al 2019). Another study suggests that the Sargassum fusiforme fucoidan can improve antioxidant status by lowering malondialdehyde levels, increasing GSH/GSSG ratio and activating Nrf2 signalling pathway in a mechanism involving the promotion of Bacteroides, Alistipes, Lactobacillus and reduction of Helicobacter in HFD-fed mice (Zhang et al 2020). Collectively, the evidence above suggests that GM is involved in the regulation of oxidative stress and its alteration can reverse obese features.…”
Section: Gm and Oxidative Stressmentioning
confidence: 99%
“…Of these, fucoidan and carrageenan are beneficial sulphated polysaccharides, which exhibit anti-obesity properties through altering the composition of gut microbiota 2 . These polysaccharides were extensively studied using high fat diet-induced obese mice and clinical trials with obese population, and these studies proved that their anti-obesity properties were involved in the reduction of Bacteroidetes / Firmicutes ratio 3 , which is a relevant marker of gut dysbiosis in obese population, increased diversity of microbiota 4 , 5 , and increase in specific gut bacteria 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%